Recent trend in microbial profile and antimicrobial susceptibility pattern of aural discharge in a tertiary care teaching hospital of Kolkata, West Bengal - Sohag Kundu; Bijan Kumar Adhikary; Ananda Sanchayeeta Mondal; Hasina Banu; Hirak Jyoti Raj; Bhaskar Ghosh (Al Ameen Journal of Medical Sciences)
Introduction: Ear discharge is a frequently occurring common problem in India subcontinent. Microbial niche and profile of middle ear infection are frequently changing scenario in different environment. Material & Methods: A cross sectional observational study conducted in otolaryngology and microbiology department following inclusion and exclusion criteria with 130 patients recruited from outpatient department. The primary objective being to assess the prevalence of local bacterial profile from ear discharge in patients with Chronic Otitis Media (COM). Microbiological investigation including characterization of drug resistance was performed in department of microbiology. Result: Escherichia coli, Klebsiella pneumonia, Proteus mirabilis, Citrobacter freundii, Pseudomonas aeruginosa, Acinetobacter baumannii, Staphylococcus aureus, CoNSare among the frequently isolated bacteria with Pseudomonas aeruginosa and Staphylococcus aureusbeing the two most commonly occurring pathogens. The gram negative isolates are ESBL, carbapenemase producers and staphylococci are all methicillin resistant. Discussion: Most of the studies in world show the same bacteriological profile. but the antibiogram differs. Indian studies have the similar findings like ours. Conclusion: Knowledge on bacteriological profile help to start empirical therapy.